Adolescents' knowledge of a peer's non‐suicidal self‐injury and own non‐suicidal self‐injury and suicidality. (21st September 2020) - Syed, S.; Kingsbury, M.; Bennett, K.; Manion, I.; Colman, I.
Abstract : Objective: Some research suggests that suicidal ideation and attempt among adolescents may be contagious – that is adolescents who are exposed to peers' suicidal behaviour are more likely to experience suicidal ideation or attempt suicide themselves. Less is known about the potential contagion effect of non‐suicidal self‐injury (NSSI). Our objective was to determine whether knowledge of a friend's NSSI is associated with adolescent's own non‐suicidal self‐injury and suicidal behaviours. Methods: Data from 1483 youth ages 14–17 years were obtained from the 2014 Ontario Child Health Study, a cross‐sectional population‐based survey of children and adolescents in Ontario, Canada. Logistic regression models were used to examine associations between knowledge of a friend's NSSI and adolescents' own self‐reported self‐injurious and suicidal behaviours. Interactions with gender, age group and presence of a mental disorder were investigated. Results: Knowledge of a friend's non‐suicidal self‐injury was significantly associated with the adolescent's own non‐suicidal self‐injury (OR = 2.03, 95% CI 1.05–3.90), suicidal ideation (OR = 3.08, 95% CI 1.50–6.30) and suicide attempt (OR = 2.87, 95% CI 1.20–6.87). Conclusion: These findings suggest an apparent contagion effect for non‐suicidal self‐injury. Awareness of a friend's self‐injurious behaviours is associated with an adolescent's own self‐injury and suicidality. Interventions aimed at preventing NSSI and suicidality should consider prevention of possible contagion at the school and/or community level.